INFORMASI, ORIENTASI PASAR, DAN IMPLEMENTASI STRATEGI DIFERENSIASI TERHADAP KUALITAS LAYANAN DALAM MENCAPAI KEUNGGULAN BERSAING (STUDI KASUS PADA RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG) - Raharjo, Susilo Toto; Poerbantoro, Heri (JURNAL BISNIS STRATEGI, 2007)
This research is conducted on the basis of, or because of, the difference of research view/ the gap research concerning influence of service quality in improving competitive advantage. Research of Churchill (1994) yields conclusion, that quality of service more is having an effect on profitability than on company competitive advantage. Whlle research of James L Wahlers (1994) and Kohli (1997) yields conclusion which much the same to, that quality of service have an effect on competitive advantage. According to Kutcher (2000), competitive advantage is also influenced by strategy implementation of differentiation. There are some factors influencing the quality of service (Servqual), for example usage of information technology and company orientation.At healthcare industry, quality of service represent key factor in improving competitive advantage. This research is done at hospital which is its service indicator still under efficiency boundary/limit, where this problem depict the quality of service which still lower and competitive advantage position less beneficial.This research use all structural functionaries/officers in all management level from board of directors till supervisor as research object. Data collecting is done with enquette method which filled by the structural officers. By using SEM, it is found that quality of service influenced by usage of information technology and market orientation. Furthermore, It is found that quality of service and implementation of differentiation strategy have an effect on competitive advantage. This research model can fulfill specified criterion of "goodness of fit.â€ Pursuant to this matter, hence suggested that company improve competitive advantage through improvement of service quality and correct implementation of differentiation strategy.